Letramento espacial por meio de games digitais - Valente, Vania Cristina Pires Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Researchers on the abilities needed by Graphic's Representation professionals conclude that the main prerequisite for its achievement is knowing reason spatially, that is to have the ability Space developed. Spatial skill is the ability to mentally design objects in two or three dimensions and manipulate them spatially maintaining its characteristics of shape, size and interelationships. This ability is necessary for the creation, representation and reading projects in Engineering. Architecture, Design and other areas of knowledge. Although essential for vocational training, there is a lack of development on the part of students joining the university and this presents a challenge for teachers, especially those dealing with design disciplines Technical and Descriptive Geometry (DG). This research analyzed the possibility of application of Digital Games present at the university for everyday of motivating and natural way, instiggating the development of Spatial Ability favoring efficient spatial thinking, that is, promoting your Spatial Literacy. The method used was the research ex-post-facto to search the existence of relations between the development of spatial ability of students playing digital games, comparing them with those who do not play. Was analyzed two groups of Drawing II Discipline of Unesp Design Course and both was found a positive differential as the Spatial skill in students who had the habit of playing digital games, especially first-person shooter games

Pesquisas sobre as competências necessárias aos profissionais das áreas de Representação Gráfica concluem que o principal pré-requisito para sua conquista é saber raciocinar espacialmente, ou seja, possuir a Habilidade Espacial desenvolvida. Habilidade Espacial é a capacidade de conceber mentalmente objetos em duas ou três dimensões e manipulá-los espacialmente mantendo suas características de forma, tamanho e inter-relações. Essa habilidade é necessária para a criação, representação e leitura de projetos nas Engenharias, Arquitetura, Design e em outras áreas do conhecimento. Embora essencial para a formação profissional, há uma carência de seu desenvolvimento por parte dos discentes, principalmente aqueles que se apresenta como um desafio para os docentes, principalmente aqueles que lidam com disciplinas de Desenho Técnico e Geometria (GD). Esta lidam com disciplinas de Desenho Técnico e Geometria Descritiva (GD). Esta pesquisa analisou a possibilidade de aplicação dos games Digitais presentes no cotidiano dos universitários para, de maneiro motivante e natural, instigar o desenvolvimento da Habilidade Espacial favorecendo o pensamento espacial eficiente, ou seja, promovendo seu letramento espacial. O método adotado foi o da pesquisa ex-post-fact por buscar a existência de relações entre o desenvolvimento da Habilidade Espacial dos alunos que jogam games digitais, comparando-os com os que não jogam. Foram analisadas duas turmas da Disciplina de Desenho II do curso de Design da Unesp e em ambas foi constatado um diferencial positivo quanto à habilidade espacial nos alunos que possuíam o hábito de jogar games digitais, principalmente os games de atirador em primeira pessoa
Spatial literacy by digital games
Keywords: Spatial skill; Descriptive geometry; Digital games; Spatial literacy; Aptidão; Percepção espacial; Geometria descritiva; Jogos eletronicos; Letramento; Ability